2015
DOI: 10.12973/eurasia.2015.1372a
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Gender Differences on Cognitive and Motivational Factors that Influence 8th Graders’ Science Achievement in Turkey

Abstract: graders' science achievement and also gender differences on factors that significantly contribute to the science achievement model. A total of 99 girls and 83 boys responded all the instruments used in this study. Results showed that girls outperformed boys on science achievement. Furthermore, regression analyses showed a model including initial conceptual knowledge, scientific reasoning, and utility value of science as independent variables best predicted science achievement. Results also showed girls and boy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 36 publications
5
15
0
5
Order By: Relevance
“…Results of national student performance assessments also reveal that girls outperform boys in science (e.g., Atalmis, Avgin, Demir, & Yildirim, 2016;Bursal, 2013;EARGED, 2009). Furthermore, this superiority is also evident in the comparisons of in-class science examinations and grades (Acar, Türkmen, & Bilgin, 2015;Boz, Yerdelen-Damar, Aydemir, & Aydemir, 2016;Bursal, 2013;Engin-Demir, 2009). Even Bursal (2013) has revealed that this gender based achievement gap widens as grade level increases.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Results of national student performance assessments also reveal that girls outperform boys in science (e.g., Atalmis, Avgin, Demir, & Yildirim, 2016;Bursal, 2013;EARGED, 2009). Furthermore, this superiority is also evident in the comparisons of in-class science examinations and grades (Acar, Türkmen, & Bilgin, 2015;Boz, Yerdelen-Damar, Aydemir, & Aydemir, 2016;Bursal, 2013;Engin-Demir, 2009). Even Bursal (2013) has revealed that this gender based achievement gap widens as grade level increases.…”
Section: Introductionmentioning
confidence: 96%
“…Atalmis, Avgin, Demir, & Yıldırım, 2016;Bursal, 2013;EARGED, 2009). Ayrıca cinsiyete dayalı bu başarı farkı, fen bilimleri dersi sınav sonuçlarında 9 ve not ortalamalarında da belirgindir (Acar, Türkmen, & Bilgin, 2015;Boz, Yerdelen-Damar, Aydemir, & Aydemir, 2016;Bursal, 2013;Engin-Demir, 2009). Hatta Bursal (2013), sınıf seviyesinin yükselmesiyle beraber cinsiyete dayalı bu başarı farkının arttığını ortaya koymuştur.…”
Section: Introductionunclassified
“…Studies with this purpose showed that female students surpassed male students on scientific yielding. Additionally, some results show that the most appropriate model that corresponds with this behavior includes the initial conceptual knowledge, scientific reasoning, and science value as variables that predict scientific accomplishment [Acar et al 2015].…”
Section: Cognitive Development and Scientific Reasoningmentioning
confidence: 92%
“…In addition to the science achievement gap, the gender science achievement gap is also observed for general science in favor of girls in Turkey (Acar et al, 2015;Atalmis, Avgin, Demir, & Yildirim, 2016;Gevrek & Seiberlich, 2014;OECD, 2014OECD, , 2016a. Gevrek and Seiberlich (2014) examined the gender gap among different parts of the science achievement distribution of PISA scores.…”
Section: Problem Statementmentioning
confidence: 99%
“…Furthermore, metacognitive skills are also considered to be good predictors of science achievement (Alpaslan, 2017;Areepattamannil, 2014;Kizilgunes, Tekkaya, & Sungur, 2009;Topçu & Yılmaz-Tüzün, 2009). Student-level motivational factors that have an effect on science achievement include but not limited to self-efficacy (Boz et al, 2016;Kalender & Berberoglu, 2009;Martin et al, 2012;Sun, Bradley, & Akers, 2012), self-concept, and perceived success (Abu-Hilal, Abdelfattah, Alshumrani, Abduljabbar, & Marsh, 2013;EARGED, 2009;Gevrek & Seiberlich, 2014; Jansen, Schroeders, & Lüdtke, 2014), enjoyment of science (EARGED, 2009;Martin et al, 2012;Ozel, Caglak, & Erdogan, 2013), and instrumental motivation to learn science (Abu-Hilal et al, 2013;Acar et al, 2015;Martin et al, 2012;OECD, 2016a;Ozel et al, 2013). On the other hand, teacher-level factors that have an effect on science achievement include student perception of instruction in terms of inquiry (Ceylan & Berberoglu, 2007;Kalender & Berberoglu, 2009;OECD, 2016b), teacher attendance to professional developmental programs (Atar, 2014;Milli E gitim Bakanlı gı, 2016;Shymansky, Wang, Annetta, Yore, & Everett, 2012), teacher support (Engin-Demir, 2009;OECD, 2016b;Sakız, 2015), and professional collaboration of teachers (Atar, 2014).…”
Section: Introductionmentioning
confidence: 99%